Possibilities for Optimizing the Accounting of Transactions for the Import of Goods with the Participation of an Intermediary - Pancheva, Stanislava (Economy and Business Yearbook, 2022)
The scientific development examines the transactions for the import of goods with the participation of an intermediary, revealing their essence and highlighting their features for tax and accounting purposes. Specific stages in their progress are distinguished and the economic operations implemented in them are highlighted. An analysis of the possibilities for accounting treatment of the investigated transactions by stages of progression is carried out with a view to its refinement and optimization. Based on the results of the analysis, a model for accounting is structured, with two approaches distinguished in it: recommended and permissible alternative. Solutions to unresolved issues identified during the testing of the model in a real environment are discussed and argued.